Konstruksi Ilmu Menurut Nashiruddin Ath-Thusi - Mahdi, Mahdi; Yunus, Firdaus M. (Tapis: Jurnal Penelitian Ilmiah, 2023)
Nashiruddin Ath-Thusi (1202-1274 M /597- 672 H) is better known as an astronomer than a philosopher, this is because he built an observatory Rasad Khanah in Maragha Azerbaijan, his work in philosophy was the endeavor and pioneer of the revival movement (revivalis), for trying to revive Ibn Sina's philosophical concept which had sunk due to the "thought" of Al-Ghazali in his criticism (Review/Cash) to Ibnu Sina's books which are more specific in the bookAl-Isyarat wa Al-Tanbihat.According to Ath-Thusi as well as the opinion of Ibn Sina states that the theory of knowledge is a concept (tasawwur) or evaluation (tashdiq); the concept itself can be obtained through definitions and can also be obtained through syllogisms. Both definitions and syllogisms are two media to achieve knowledge. Conceptually in philosophical thought, neo-Platonic teachings, Ibn Sina, Suhrawardi, and Aristotle seem to greatly color the philosophical thought of ath-Thusi. From various aspects of the study, Ath-Thusi's philosophical thoughts are more reflected in ethical issues, household ethics, and political ethics. While the axiology of the philosophy of science, according to Nasiruddin Ath-Thusi, science is more about aspects and fields that are needed at this time, and provide benefits and bring good values ​​later in the hereafter, and epistemologically must be sourced from Kitabullah.